A SYNTACTIC AND SEMANTIC ANALYSIS ON MOTORCYCLE SLOGANS - Dwi Noviyanti; Mhd Nur; Khoirul Huda (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2017)
Language has functioned as a media communication. Language has a very important role as a means of communication; with language, human beings can express most of their thoughts, feelings, and knowledge to the others in their daily lives. Linguistics Description refers to the exploration and classification of linguistic features of a given text and the linguistic features. Besides, linguistics is a study of the language and the social aspect of society. The slogan is an imaging sign of company. It is a phrase that comes and goes with particular lines of products on all its adverts whatever the campaign. Motorcycle slogan is a memorable motto or phrase in creating product branding as a repetitive expression of an idea or purpose. This study is specified in the analysis of syntax and semantics on motorcycle slogan in Indonesia. This study had three problems statement, they were: what types of the slogan used in motorcycle slogans, what the syntax are used on motorcycle slogans and what the semantics are used on motorcycle slogans. In this research, the researcher used qualitative research design. The researcher took the motorcycle slogans as a source of data. The researcher only focuses on motorcycle slogans in Indonesia, especially Honda, Yamaha, and Suzuki product. Based on this study, the researcher found 7 descriptive slogans, 15 superlative slogans, and 6 provocative slogans. The researcher could not find kind of imperative slogan. From the description above, the researcher concluded that most of the motorcycle slogan used superlative slogans. Most motorcycle slogans used superlative types. In syntax, the researcher found 22 phrases (21 noun phrases, 1 verb phrase), and 6 slogans were not phrases but sentences. So, noun phrase was found dominantly in the motorcycle slogans. In semantics, the researcher found 9 denotative meanings and 19 connotative meanings. So, connotative meanings were found dominantly in the motorcycle slogans. Based on the results of the study, it could be concluded that each motorcycle slogans had its own type and meaning. Motorcycle slogans used by companies to promote their motorcycle to the custom motorcycle products.